Implementasi Peraturan Pengadaan Barang/Jasa untuk Percepatan Pembangunan Kesejahteraan di Provinsi Papua dan Provinsi Papua Barat di Dinas Pendidikan Kabupaten Supiori - Alberto Michael Korwa; Djunaedi Djunaedi; Fatmawada S (Journal of Innovative and Creativity, 2025)
Government procurement of goods/services plays a crucial role in accelerating development and improving public welfare, including in the provinces of Papua and West Papua. However, the implementation of procurement regulations still faces challenges in terms of transparency, accountability, and effectiveness. This study employed a qualitative approach with a case study method in the Supiori Regency Education Office. Data were collected through interviews, observations, and document reviews, then analyzed descriptively to evaluate the implementation of procurement regulations. The findings indicate that the implementation of procurement regulations in the Supiori Regency Education Office has been running according to procedure, but there are still obstacles such as limited human resources, lack of technical understanding, and coordination constraints between related parties. This study concludes that although procurement regulations have been implemented, their effectiveness in supporting the acceleration of welfare development is not optimal. Improvement of apparatus capacity, strengthening of the monitoring system, and synergy between institutions are needed so that implementation can be more effective and have a real impact on the community.